Influence of atrial fibrillation type on outcomes of ablation vs. drug therapy: results from CABANA . Issue 9 (31st May 2022) - Monahan, Kristi H; Bunch, T Jared; Mark, Daniel B; Poole, Jeanne E; Bahnson, Tristram D; Al-Khalidi, Hussein R; Silverstein, Adam P; Daniels, Melanie R; Lee, Kerry L; Packer, Douglas L; ,
Abstract: Aims: Influence of atrial fibrillation (AF) type on outcomes seen with catheter ablation vs. drug therapy is incompletely understood. This study assesses the impact of AF type on treatment outcomes in the Catheter Ablation vs. Antiarrhythmic Drug Therapy for Atrial Fibrillation Trial (CABANA). Methods and results: CABANA randomized 2204 patients ≥65 years old or <65 with at least one risk factor for stroke to catheter ablation or drug therapy. Of these, 946 (42.9%) had paroxysmal AF (PAF), 1042 (47.3%) had persistent AF (PersAF), and 215 (9.8%) had long-standing persistent AF (LSPAF) at baseline. The primary endpoint was a composite of death, disabling stroke, serious bleeding, or cardiac arrest. Symptoms were measured with the Mayo AF-Specific Symptom Inventory (MAFSI), and quality of life was measured with the Atrial Fibrillation Effect on Quality of Life (AFEQT). Comparisons are reported by intention to treat. Compared with drug therapy alone, catheter ablation produced a 19% relative risk reduction in the primary endpoint for PAF adjusted hazard ratio [aHR]: 0.81 [95% confidence interval (CI): 0.50, 1.30], and a 17% relative reduction for PersAF (aHR: 0.83, 95% CI: 0.56, 1.22). For LSPAF, the ablation relative effect was a 7% reduction (aHR: 0.93, 95% CI: 0.36, 2.44). Ablation was more effective than drug therapy at reducing first AF recurrence in all AF types: by 51% for PAF (aHR: 0.49, 95% CI: 0.39, 0.62), by 47% for PersAF (aHR: 0.53, 95% CI: 0.43, 0.65), and by 36% for LSPAF (aHR 0.64, 95% CI 0.41, 1.00). Ablation was associated with greater improvement in symptoms, with the mean difference between groups in the MAFSI frequency score favouring ablation over 5 years of follow-up in all subgroups: PAF had a clinically significant −1.9-point difference (95% CI: −1.2 to −2.6); PersAF a −0.9 difference (95% CI: −0.2 to −1.6); LSPAF a clinically significant difference of −1.6 points (95% CI: −0.1 to −3.1). Ablation was also associated with greater improvement in quality of life in all subgroups, with the AFEQT overall score in PAF patients showing a clinically significant 5.3-point improvement (95% CI: 3.3 to 7.3) over drug therapy alone over 5 years of follow-up, PersAF a 1.7-point difference (95% CI: 0.0 to 3.7), and LSPAF a 3.1-point difference (95% CI: -1.6 to 7.8). Conclusion: Prognostic treatment effects of catheter ablation compared with drug therapy on the primary and major secondary clinical endpoints did not differ consequentially by AF subtype. With regard to decreases in AF recurrence and improving quality of life, ablation was more effective than drug therapy in all three AF type subgroups. ClinicalTrials.gov Identifier: NCT00911508 Graphical Abstract: Graphical Abstract Primary endpoint outcomes and AF recurrence by AF type in the CABANA trial. Top panels show Kaplan–Meier curves for the CABANA primary endpoint (total mortality, disabling stroke, serious bleeding, or cardiac arrest) for patients with ( A ) paroxysmal, ( B ) persistent, or ( C ) long-standing persistent atrial fibrillation.